Entrepreneurship Culture: Export Technologies, Strategies and Promoting Ukrainian Goods to the Market of the Ottoman Empire (Late 19th–Early 20th Centuries) - Shandra, Irina; Temirova, Nadiia; Birova, Olha (Journal of History Culture and Art Research, 2020)
The article examines export techniques, strategies, and promoting Ukrainian goods to the market of the Ottoman Empire in the late 19th – early 20th centuries. That historical period was chosen not by chance, but because there was a rapid economic recovery in Ukraine then. Although there was no a state but Ukrainian was part of the Russian Empire, a corporate community of Ukrainian entrepreneurs (representative organizations) was formed, and Ukrainian lands became the leading production region of the empire, it linked all those involved in trade relations with grains, sugar, coal, and mineral resources. The excess of production over the volume of the domestic consumer market encouraged entrepreneurs to export these goods, primarily to the nearest foreign markets. The market of the Ottoman Empire was determined as a priority in that respect. The study of the export direction of commercial activity of Ukrainian entrepreneurs became possible as a result of attracting a wide range of sources including “Government and business statistical directories, office documents of representative organizations, articles from periodicals of that time, archival materials”. Export techniques of Ukrainian businessmen were analyzed in the article as one of the components of business culture, and consists in introducing organizational and logistical techniques for export tasks, studying global experience, and using the most successful and effective mechanisms to influence the process of invading foreign markets. The paper shows that Ukrainian entrepreneurs had resorted to a variety of tools to promote their products including renting space in Turkey and participating in the "Floating Exhibition". The article concludes that, despite all efforts, Ukrainian entrepreneurs lost in competition with more developed countries and they had to pay attention to the increased domestic demand. The idea of Ukrainian trade and industry to organize a permanent trade mission in Istanbul in the form of a chamber of commerce, which originated in the early 20th century, it is implemented at the present stage of mutually beneficial partnership between Ukraine and Turkey.